Faktor - faktor yang mempengaruhi kunjungan ibu balita ke Posyandu Desa Melayu Besar Kabupaten Rokan Hilir - Yusdiana Yusdiana; Armoni Suci Dewi; Fathiya Azka Putri; Ria Permata Sari (Jurnal Ilmu Kedokteran, 2023)
Integrated Healthcare Center (Posyandu) provides access to the community for basic health access, especially for children under five. Indonesian Ministry of Health targeting children under five visit coverage at Posyandu by 90%. Children under five visit coverage to Posyandu at Tanah Putih Tj. Melawan public health center in 2019 only 37.2% of children under five visit coverage at Posyandu Melayu Besar by 42.8%. It is far from the expected target. The objective of this study is to determine factors influencing mother visitation to posyandu Melayu Besar, Rokan Hilir district. Fifty five mothers who have children between 1 – 5 years old were included in this study with accidental sampling. This observational study using a cross-sectional design. This study was conducted from August-October 2022. Collecting data using questionnaire and registration book for posyandu for visitation data. We analyze with univariate for distribution frequencies and bivariate using chi-square for relations. Most of the mothers who bring their children to posyandu are not working and high school graduates, with distance from home to posyandu not being a significant variable. Knowledge level about posyandu mostly in the “good” category by 60%. Number of children under five visit in the “routine” category by 61.8%. There is a correlation with mother visitation. Chi-Square (X2) analysis earned p-value = 0,004 compare to α = 5% mean p < 0,05. In conclusion, there is a correlation between the mother’s knowledge with number of children under five visitation to posyandu.